Pengembangan Media Sex Education Book Untuk Meningkatkan Pemahaman Pendidikan Seksual Pada Anak Usia Dini - Nur Nurbaiti; Aip Saripudin; Masdudi Masdudi (AWLADY : Jurnal Pendidikan Anak, 2022)
ABSTRACTThe understanding of sexual education for children aged 5-6 years at RA Nur Kamal has not developed optimally, besides that the media related to sexual education is still limited in its availability. This study aims to develop sexual education using the Sex Education Book media in order to increase the understanding of sexual education for children aged 5-6 years in RA. This study uses the Research and Development method by using data collection techniques in the form of observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive qualitative and descriptive quantitative. The results of this study are a media Sex Education Book that has been declared "Eligible" to be used to improve understanding of children's sexual education, with a feasibility score of 95.75% media validation, 100% material validation, and 100% language validation. User assessment obtained the results of eligibility of 97.22% homeroom teachers, 100% principals, and 100% accompanying teachers. In addition, from the Sex Education Book media trial, it obtained an increase score of 80% and entered the BSB category (Extremely Developed). These results indicate that the understanding of sexual education in children increased significantly compared to the results before using the media which obtained a percentage score of 54.28% in the BSH category (Developing as Expected). Keywords: sex education book, sexual education, early childhood    ABSTRAKPemahaman pendidikan seksual pada anak usia 5-6 tahun di RA Nur Kamal belum berkembang secara optimal, selain itu media yang berkaitan dengan pendidikan seksual masih terbatas kesediaanya. Penelitian ini bertujuan untuk mengembangkan pendidikan seksual menggunakan media Sex Education Book agar dapat meningkatkan pemahaman pendidikan seksual anak usia 5-6 tahun di RA. Penelitian ini menggunakan metode Research and Development dengan menggunakan teknik pengumpulan data berupa observasi, wawancara, angket dan dokumentasi. Teknik analisis data yang digunakan yaitu deskriptif kualitatif dan deskriptif kuantitatif. Hasil dari penelitian ini yaitu sebuah media Sex Education Book yang telah dinyatakan “Layak” digunakan untuk meningkatkan pemahaman pendidikan seksual anak, dengan skor kelayakan 95,75% validasi media, 100% validasi materi, dan 100% validasi bahasa. Penilaian pengguna memperoleh hasil kelayakan sebesar 97,22% guru wali kelas, 100% kepala sekolah, dan 100% guru pendamping. Selain itu, dari uji coba media Sex Education Book memperoleh skor peningkatan sebesar 80% dan masuk ke dalam kategori BSB (Berkembang Sangat Baik). Hasil tersebut menunjukan bahwa pemahaman pendidikan seksual pada anak meningkat secara signifikan dibandingkan dengan hasil sebelum menggunakan media yang memperoleh skor persentase sebesar 54,28% kategori BSH (Berkembang Sesuai Harapan). Kata Kunci:  sex education book, pendidikan seksual, anak usia dini